Green Synthesis of Sulphuric Acid Based on "Geber's Method": A Detailed Aspen Plus Simulation - Abubakar, Abdulhalim Musa; Lawan, Bukar; Saad, Mohamed; Umdagas, Luqman Buba; Abbas, Azhar; Shettima, Habib Muhammad; Mönnig, Ronny; Kareem, Semiu Adebayo (Fine Chemical Engineering, 2024)
Sulfuric acid (H2SO4) has a wide range of applications, but its current synthesis route via the contact process negatively impacts the atmospheric environment with harmful gaseous pollutants. Thus, based on the non-random two-liquids (NRTL) thermodynamic method, this study presents a detailed Aspen Plus V8.8 simulation of the green synthesis route of H2SO4 based on Geber's method developed already in the 18th century. The research investigates the efficiency and energy dynamics of the process through the analysis of key process parameters such as reactor's heat duty, vapor fraction, and molar extent of reaction in the selected configuration, using green vitriol (FeSO4∙7H2O) as a natural raw material. This study presented a novel manufacturing route that resulted in H2SO4 of 85.76% purity (33.71 kg/h), considering the chosen parameter space. The results highlight the impact of reactant component molar yield and fractional conversion of iron (II) sulfate (FeSO4) on heat duty and the optimal molar extent for maximizing H2SO4 production in a series of equilibrium reactors. In addition, appropriate operational parameters for the synthesis process were carefully specified, offering a pathway towards sustainable and eco-friendly H2SO4 production, which should emit zero greenhouse gases. Further optimization of the reactor conditions, can help maximize the yield of H2SO4, while minimizing energy consumption and byproduct formation. Developing advanced wastewater treatment units to purify the wastewater stream containing trace amounts of H2SO4 and dissolved sulfur trioxide (SO3) can mitigate environmental impact and ensure compliance with regulatory standards.